Production and validation of a polyclonal serum against bovine FSH receptor - Marelli, Belkis Ester (2018)
In ovarian granulosa cells, follicle-stimulating hormone (FSH) regulates the proliferation and differentiation events required for follicular growth and oocyte maturation. FSH actions are mediated exclusively through the FSH receptor (FSHR). In cattle, the FSHR gene expression pattern during folliculogenesis and the implications of this receptor in reproductive disorders have been extensively studied. However, the limited availability of specific antibodies against bovine FSHR has restricted FSHR protein analysis. In the present study, we developed an anti-FSHR polyclonal serum by using a 14-kDa peptide conjugated to maltose binding protein. The antiserum obtained was characterized by western blot of protein extracts from bovine follicles, BGC-1 cells and primary cultures of granulosa cells stimulated with testosterone. Also, the blocking effect of serum on estradiol secretion and cell viability after gonadotropin stimulus was characterized in a functional in vitro assay. A 76-kDa protein, consistent with the predicted molecular size of full-length FSHR, was detected in ovarian tissue. Besides, two immunoreactive bands of 60-kDa and 30-kDa (only in cultured cells) were detected. These bands would be related to some of the isoforms of the receptor. Therefore, immunohistochemical assays allowed detecting FSHR in the cytoplasm of granulosa cells and an increase in its expression as follicles progressed from primordial to large preantral follicles. These results suggest that the anti-FSHR serum here developed has good reactivity and specificity against the native FSHR. Therefore, this antiserum may serve as a valuable tool for future studies of the biological function of FSHR in physiological conditions as well as of the molecular mechanism and functional involvement of FSHR in reproductive disorders.